Antimicrobial Resistance Situation in SCANU of Faridpur Medical College Hospital, a Tertiary Level Hospital in Bangladesh (Faridpur Medical College Journal, 2020)
Considering the high risk of neonatal sepsis in low and middle-income countries, empirical antibiotic therapy is commonly employed in most cases to clinically suspected septic neonates without the aid of culture and antibiotic sensitivity report. Increasing antimicrobial resistance is posing a threat to these practices and urges the obligation for understanding the causative organisms and their changing resistance pattern at the local level. Aim of this study was to identify the pathogens responsible for neonatal sepsis and understand their current antimicrobial resistance pattern. This prospective study was undertaken in the Special Care Newborn Unit of the Faridpur Medical College Hospital from October 2017 to November 2018. Venous blood culture and antimicrobial susceptibility of 56 suspected neonatal sepsis cases were studied. Among the 56 clinically suspected cases 86% had culture positive isolates in the specimen. Predominant isolates were Klebsiella (42%) and coagulase-negative staphylococci (25%). Of all the identified bacteria, 88% were resistant to >_ 3 classes of antibiotics. Eighty-five percent of Klebsiella isolates were found to be carbapenem-resistant along with 100% of E. coli isolates and 95% of Klebsiella isolates had possible extended spectrum b -lactamase production. Seventy-five percent of Acinetobacter isolates were multidrug-resistant and 100% of coagulase-negative staphylococci were methicillin resistant. The array of causative organisms and their increasing resistance to commonly practiced antibiotics are alarming. It is urgent to develop strategies focusing on all healthcare levels to cease the spread of antimicrobial resistance in an effort to reduce the burden of neonatal sepsis.Faridpur Med. Coll. J. Jan 2020;15(1): 28-33